(untitled) (Research, Society and Development, 2024)
The microbiota is made up of several microorganisms, bacteria, viruses and fungi that inhabit the human body, carrying out mutualistic processes. This mechanism directly interferes with the digestion and absorption of nutrients, protection against pathogenic organisms, regulation of the immune system, and enzymatic functions that act as stimulators and precursors of substances involved in various metabolic processes of the host. This review aims to describe the functions of the gut microbiota, together with the existing microorganisms of the human gut, which is one of the largest in diversity, number and functions performed. Studies were analyzed using databases such as Periódico CAPES, SciELO and LILACS and PubMed, covering publications between 1990 and 2022. The gut microbiota is responsible for maintaining gut homeostasis, in which it prevents the development of pathogens and infectious agents. There is a relationship between increased inflammatory rates and gut dysbiosis, which may be associated with improper diets, consumption of toxic and chemical products, as well as genetic and environmental factors that can suppress or trigger the increase in harmful bacteria. The determinants of the gut microbiota were addressed. The relationship between the brain and the gut and the influence of the microbiota on obesity, the immune system, the development of neurological diseases and cancer were discussed. The role of the microbiota in pseudomembranous colitis has been presented. It was possible to understand that dysbiosis triggers several innate and adaptive immune responses that can develop the formation of several harmful processes for the host. It is concluded that the intestinal microbiota plays an essential role in maintaining the homeostasis of the intestine through the host’s immune system, and evolves with it, influencing the metabolism, physiology and development of the immune system, while disruption of the microbial community can result in chronic diseases.